Counselling Psychology and Under-Represented Groups: A Vision for Advocacy as Mutual Transformation - Kwee, Janelle L. (Canadian Journal of Counselling and Psychotherapy, 2020)
The discipline of counselling psychology in Canada has aligned consistently with social justice principles. Consistent with this, a working group at the 2018 Canadian Counselling Psychology Conference was assigned to consider the role of Canadian counselling psychology in advocating for the needs of members of under-represented groups. This brief report captures insights from the working group and focuses on two primary themes: a critical reformulation of advocacy as mutual transformation for personal and social change and a need to engage with change processes at multiple levels. The group conceptualized effective advocacy as recentring historically marginalized perspectives while decentring “expert” roles and traditionally dominant perspectives.